Immediate Moderate Intensity Treadmill Exercise After Restraint Stress Induced ERK-mediated Anxiety and Depression - Heon Seok (The Asian Journal of Kinesiology, 2018)
PURPOSE Chronic stress cause physical and mental function disorders such as anxiety and depression. One of the effective ways to relieve this stress is regular moderate intensity exercise. However effect of exact role of moderate intensity exercise on physical and mental function is not clear. This study aim to investigate the effect of immediate moderate intensity exercise after stress on anxiety, depression-like behavior and motor ability. METHODS Six-week-old male wister rat were divided into three group which were control(CT) group, restraint stress (RS) group and treadmill exercise after restraint stress (EX) group. RS and EX group were subjected to restraint stress (1h/day) for 5 days, while CT group were stay in normal condition. Immediate after restraint stress, EX group were subjected to treadmill-running (30min/day) for 5 days immediate after restraint stress. Free moving tests and open field tests were used to analyze behavior and athletic competence such as anxiety and depression, and phosphorylation levels of ERK were assessed using western blotting of the brain hippocampus. RESULTS In free moving test, freezing time of EX group were increased compared to RS group(p<.05) and CT group(p<.05). On the other hand, Velocity of EX group were decreased compared to RS group(p<.05) and CT group(p<.05). In open field test, velocity, distance and frequency in center of RS group were lower than CT group(p<.05) and EX group were lower than ST group(p<.01). Phosphorylation of ERK were increased on EX group. CONCLUSIONS Immediate moderate intensity treadmill exercise after restraint stress increased anxiety and depression-like behavior and decreased motor ability. Furthermore, the activity of ERK protein associated with stress and depression was increased by immediate exercise after stress. The results suggest that immediate exercise after stress can lead to mental and physical depression.